Analisis Pengaruh Tingkat Pengangguran, Tingkat Pendidikan dan Investasi Dalam Negeri Terhadap Pertumbuhan Ekonomi Riau - Aswanto, Aswanto; Hsb, Mhd Suleman; Mukson, Mukson; Edward, Yurnal; Zulfitri, Zulfitri; Ikhsan, Wandi Nur (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Economic growth is the development of activities in an economy that causes goods and services to increase from year to year and the prosperity of society to increase in the long term. In this study, there are several factors that influence it, namely the unemployment rate, education level and investment. Unemployment is a condition of someone who has not worked and is still looking for work. Education is a human resource capital that has a very large influence both for himself and for an economy. Investment is something that is very important in creating capital accumulation which can ultimately create economic growth. The purpose of this study is to analyze and determine the effect of the unemployment rate, education level and investment on the economic growth of Riau Province. The data analysis method uses multiple regression with the Eviews 13 application analysis tool. The results of this study indicate that the unemployment rate, education level and investment have a significant influence on economic growth as evidenced by the determination coefficient value of 0.9142 or 91.42%. So it can be interpreted as having a large influence on economic growth.